Pharmacokinetics and Bioequivalence of Rasagiline Tablets in Chinese Healthy Subjects Under Fasting and Fed Conditions: An Open, Randomized, Single-Dose, Double-Cycle, Two-Sequence, Crossover Trial - Li, Yinjuan; Qi, Lu; Bai, Haihong; Liu, Ying; Fan, Rongxia; Tu, Yongrui; Sun, Yongqiang; Wang, Juxiang; Qi, Qi; Feng, Xiaohui; Zhou, Da; Wang, Xinghe (Frontiers in Pharmacology, 2020)
Objective This study evaluated the pharmacokinetics, safety, and bioequivalence (BE) of 2 formulations of rasagiline tablets in healthy Chinese subjects under fasting and fed conditions. Methods An open, randomized, single-dose, double-cycle, two-sequence, self-crossover pharmacokinetic study in healthy Chinese subjects under fasting and high-fat postprandial conditions was performed. A total of 108 healthy subjects (36 in the fasting group and 72 in the postprandial group) were recruited. In each cycle of the study under both conditions, subjects received a single oral dose of 1 mg of a test or reference preparation of rasagiline tablets (1 mg each). A washout period of 3 days was observed. Blood samples were obtained up to 10 hours post-intake. Primary endpoints were the BE of major pharmacokinetic parameters (AUC0-t and AUC0-∞) and the maximum observed serum concentration (Cmax). Secondary endpoints were safety parameters. Results The 90% confidence interval (CI) of the geometric mean ratio (GMR) of the test drug versus the reference drug for rasagiline was 94.16% to 105.35% for the AUC0-t under fasting conditions and 99.88% to 107.07% under postprandial conditions. The 90% CIs for the AUC0-∞ were 93.55% to 105.01% and 99.59% to 107.05% under fasting and postprandial conditions, respectively. The 90% CIs for the Cmax were 88.26% to 108.46% and 89.54% to 118.23% under fasting and postprandial conditions, respectively. The 90% CIs for the test/reference AUC ratio and Cmax ratio were within the acceptable range (0.80–1.25) for BE. In this BE study, there were no serious adverse events (AEs). Conclusion BE between the test and the reference products was established in both fasting and postprandial conditions. The two formulations of rasagiline showed good tolerability and a similar safety profile.